Pex14p Phosphorylation Modulates Import of Citrate Synthase 2 Into Peroxisomes in Saccharomyces cerevisiae - Schummer, Andreas; Maier, Renate; Gabay-Maskit, Shiran; Hansen, Tobias; Mühlhäuser, Wignand W. D.; Suppanz, Ida; Fadel, Amir; Schuldiner, Maya; Girzalsky, Wolfgang; Oeljeklaus, Silke; Zalckvar, Einat; Erdmann, Ralf; et al. (Frontiers in Cell and Developmental Biology, 2020)
The peroxisomal biogenesis factor Pex14p is an essential component of the peroxisomal matrix protein import machinery. Together with Pex13p and Pex17p, it is part of the membrane-associated peroxisomal docking complex in yeast, facilitating the binding of cargo-loaded receptor proteins for translocation of cargo proteins into the peroxisome. Furthermore, Pex14p is part of peroxisomal import pores. The central role of Pex14p in peroxisomal matrix protein import processes renders it an obvious target for regulatory mechanisms such as protein phosphorylation. To explore this possibility, we examined the state of Pex14p phosphorylation in Saccharomyces cerevisiae. Phos-tag-SDS-PAGE of Pex14p affinity-purified from solubilized membranes revealed Pex14p as multi-phosphorylated protein. Using mass spectrometry, we identified 16 phosphorylation sites, with phosphorylation hot spots located in the N- and C-terminal regions of Pex14p. Analysis of phosphomimicking and non-phosphorylatable variants of Pex14p revealed a decreased import of GFP carrying a peroxisomal targeting signal type 1, indicating a functional relevance of Pex14p phosphorylation in peroxisomal matrix protein import. We show that this effect can be ascribed to the phosphomimicking mutation at serine 266 of Pex14p (Pex14p-S266D). We further screened the subcellular distribution of 23 native GFP-tagged peroxisomal matrix proteins by high-content fluorescence microscopy. Only Cit2p, the peroxisomal isoform of citrate synthase, was affected in the Pex14p-S266D mutant, showing increased cytosolic localization. Cit2p is part of the glyoxylate cycle, which is required for the production of essential carbohydrates when yeast is grown on non-fermentable carbon sources. Pex14p-S266 phosphosite mutants showed reversed growth phenotypes in oleic acid and ethanol with acetyl-CoA formed in peroxisomes and the cytosol, respectively. Overexpression of Cit2p rescued the growth phenotype of yeast cells expressing Pex14p-S266D in oleic acid. Our data indicate that phosphorylation of Pex14p at S266 provides a mechanism for controlling the peroxisomal import of Cit2p, which helps S. cerevisiae cells to adjust their carbohydrate metabolism according to the nutritional conditions.